Trend of Head and Neck Cancers in a National Tertiary Cancer Hospital of Nepal from 2012 to 2017 - Shrestha, Gambhir; Siwakoti, Bhola; Mulmi, Rashmi; Gautam, Dejkumar (South Asian Journal of Cancer, 2021)
Introduction Head and neck cancers (HNCs) are increasing in Nepal and have become a major public health issue. This study aims to describe the trend of HNCs in a national tertiary cancer hospital in Nepal.Methods This was a cross-sectional study with secondary data analysis conducted at B.P Koirala Memorial Hospital, Chitwan, Nepal. The data were obtained from the medical record section and included all new HNC cases registered from 2012 to 2017. Analysis was done using Statistical Package for Social Sciences version 17. Subgroup analysis was done according to age, gender, site, and year.Results A total of 4,582 new HNCs were registered, of which 3,097 (67.6%) were males and 1,482 (32.4%) were females. Lip and oral cavity cancers (46.5%) were the most common HNCs followed by tonsil and pharynx (18.0%) and larynx (15.8%). The trend of HNCs shows a steady rise in incidence with difference according to the sites. HNCs were more common among males than females except for thyroid cancer. The most common age group was 60 to 74 years.Conclusions The trend of HNCs is increasing in Nepal especially oral cancers. Awareness of risk factors, effective screening programs, and comprehensive treatment should be focused to decrease the burden of HNCs.
Keywords: head and neck cancers; trend; Nepal